PENERAPAN METODE PEMBELAJARAN BERBASIS KOLABORASI INTERAKTIF DAN PARTISIPATIF TERHADAP KETERAMPILAN MEMBACA PUISI PESERTA DIDIK KELAS VIII SMP PERINTIS 29 SEMARANG - Siti Fatimah; Najwa Qurrota A’yun; Agus Wismanto (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2026)
This study is motivated by the low level of students’ poetry reading skills caused by limited active engagement in the learning process, and aims to determine the effectiveness of an interactive and participatory collaborative learning method in improving the poetry reading skills of eighth-grade students at SMP Perintis 29 Semarang. This research employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model, involving 13 students selected through purposive sampling. Data were collected through pretest and posttest as well as classroom observation. The results indicate a significant improvement in students’ poetry reading skills, as evidenced by the increase in the average score from 58.46 in the pretest to 83.84 in the posttest. In addition, improvements were observed in affective and psychomotor aspects, including students’ activeness, self-confidence, and collaboration skills. Enhancement was also found in intonation and pronunciation, although expressive appreciation still requires further development. These findings suggest that the interactive and participatory collaborative learning method, grounded in constructivist theory, is capable of creating a more interactive, meaningful, and student-centered learning environment, and thus has the potential to serve as an alternative instructional strategy for improving students’ poetry reading skills.